2011
DOI: 10.1074/jbc.m111.300178
|View full text |Cite
|
Sign up to set email alerts
|

Blm10 Protein Promotes Proteasomal Substrate Turnover by an Active Gating Mechanism

Abstract: Background: Association of the proteasome core with activators regulates proteasome activity. Results: Blm10 association increases proteasome activity toward peptides and the unstructured proteasome substrate tau-441. This process is mediated by the C terminus of Blm10. Conclusion: C-terminal docking-mediated proteasome activation by Blm10 facilitates the turnover of peptide and protein substrates. Significance: Blm10 contributes to the regulation of proteasome activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(116 citation statements)
references
References 52 publications
5
110
0
1
Order By: Relevance
“…Recognition that the C terminus of PI31 features an HbYX motif characteristic of multiple proteasome activators provides new insight to possible mechanisms of PI31 action (11). Surprisingly, we found that short peptides corresponding to the PI31 HbYX-containing C terminus activate the 20 S proteasome, presumably by inducing a gate-opening mechanism similar to that documented for HbYX peptides of established proteasome activators (20,(22)(23)(24)(25)(26). Thus, inhibition of proteasome activity by intact PI31 suggests that other structural elements of PI31may occlude the HbYX-induced open gate and physically impede passage of substrates.…”
Section: Discussionmentioning
confidence: 80%
“…Recognition that the C terminus of PI31 features an HbYX motif characteristic of multiple proteasome activators provides new insight to possible mechanisms of PI31 action (11). Surprisingly, we found that short peptides corresponding to the PI31 HbYX-containing C terminus activate the 20 S proteasome, presumably by inducing a gate-opening mechanism similar to that documented for HbYX peptides of established proteasome activators (20,(22)(23)(24)(25)(26). Thus, inhibition of proteasome activity by intact PI31 suggests that other structural elements of PI31may occlude the HbYX-induced open gate and physically impede passage of substrates.…”
Section: Discussionmentioning
confidence: 80%
“…PA200 also plays a role in the maintenance of glutamine/glutamate homeostasis in mammalian cells (21). In addition, overexpression of BLM10 in yeast causes growth defects on nonfermentable carbon sources at elevated temperatures (14); recently, increased frequency of cells with dysfunctional mitochondria in cells lacking BLM10 was reported (22). These observations indicate that the cellular functions ofBlm10/PA200 proteasomes might be related to the regulation of metabolic adaptation and stress response.…”
mentioning
confidence: 83%
“…Furthermore, the inhibition of the proteasome-associated deubiquitinating enzyme Usp14 promotes tau degradation 94 . In vitro, the proteasome activator Blm10 accelerates degradation of unstructured tau 95 . Tau clearance is blocked by FK506 binding protein 51 kDa (FKBP51), which forms a chaperone complex with Hsp90 that prevents tau degradation resulting in tau oligomerization 96 .…”
Section: Loss Of Clearance Mechanisms As a Determinant Of Ageingmentioning
confidence: 99%